2020
DOI: 10.26630/rj.v14i1.2138
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Keracunan Pestisida Pada Petani Hortikultura Di Kabupaten Lampung Barat

Abstract: Pesticide poisoning is still an important health problem in agricultural areas, especially horticultural agriculture. Various chronic health effects can be caused by long-term exposure to pesticides. This study aims to determine the risk factor of pesticide poisoning in horticultural farmers in West Lampung Regency. The study used a cross sectional design which was conducted in four different areas as the center of horticulture agriculture, West Lampung Regency, Lampung Province. The study involved 289 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
1
9
0
3
Order By: Relevance
“…These results are in accordance with research in Tejosari Village, it is known that there is no significant relationship between the duration of spraying and the health complaints of farmers (Runia, 1993). These results are in line with previous research in Balik Bukit District, West Lampung Regency, which found that there was no relationship between the duration of spraying and the health complaints of farmers (Yushananta, Melinda, Mahendra, Ahyanti, & Anggraini, 2020). According to the Minister of Manpower Regulation No.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in accordance with research in Tejosari Village, it is known that there is no significant relationship between the duration of spraying and the health complaints of farmers (Runia, 1993). These results are in line with previous research in Balik Bukit District, West Lampung Regency, which found that there was no relationship between the duration of spraying and the health complaints of farmers (Yushananta, Melinda, Mahendra, Ahyanti, & Anggraini, 2020). According to the Minister of Manpower Regulation No.…”
Section: Discussionsupporting
confidence: 91%
“…Selain itu, penggunaan cara kimia dengan penyemprotan pestisida (Wahyuni, Rini, Kasatriyanto, Purwoko, & Rachmat, 2017). Namun penggunaan pestisida dapat memberikan dampak negatif seperti keracunan, polusi terhadap lingkungan, resiko terhadap kesehatan dan efek karsinogenik (Ilmiawati & Reza, 2019;Rahmasari & Musfirah, 2020;Yushananta, Melinda, Mahendra, Ahyanti, & Anggraini, 2020).…”
Section: Pendahuluanunclassified
“…Fungisida sintetis dapat menyebabkan akumulasi bahan kimia dan penurunan kualitas air serta berbahaya bagi kesehatan konsumen akibat residu bahan kimia pada produk pertanian (Dalimunthe & Arief, 2017). Yushananta et al (2020) melaporkan bahwa terjadi sekitar 5 juta laporan keracunan akibat residu pestisida di dunia dengan 4,4% dilaporkan mengalami kematian setiap tahunnya. Dampak berkepanjangan dari penggunaan fungisida sintetis adalah fungi patogen yang resisten terhadap fungisida sintetis tertentu (Suwastini et al, 2020).…”
Section: Pendahuluanunclassified